Magnetite-loaded rice husk biochar promoted the denitrification performance of Aquabacterium sp. XL4 under low carbon to nitrogen ratio: Optimization and mechanism. (March 2022) - Xu, Liang; Su, Junfeng; Ali, Amjad; Huang, Tinglin; Yang, Yuzhu; Shi, Jun; Liang, Enlei
Graphical abstract: Highlights: A magnetite (Fe3 O4 )-loaded rice husk biochar (MRHB) was prepared at 500 °C. MRHB promoted the denitrification efficiency of strain XL4 at low C/N ratio. Humic-like molecule produced by MRHB played a promoting role in denitrification. The electron transfer efficiency of strain XL4 enhanced greatly by MRHB. Magnetite provided extra electron donors for the denitrification of strain XL4. Abstract: The removal of nitrate (NO3 − -N) under the low carbon to nitrogen (C/N) ratio is a widespread issue. Here in, a modified biochar (MRHB) was prepared by combining rice husk and magnetite to promote the denitrification performance of Aquabacterium sp. XL4 under low C/N ratio. In addition, when the modified H2 O2 concentration was 0.6 mM, the dosage was 5.0 g L −1, the C/N ratio was 1.5, and the pH was neutral, the nitrate removal efficiency is 97.9%. Fluorescence excitation-emission matrix spectra (3D-EEM) showed that the metabolism of strain XL4 was stable under optimal conditions. Furthermore, the results of flow cytometry (FC) showed that the amounts of intact cells with MRHB was excellent. The measurement of cytochrome c concentration, total membrane permeability (Tmp ), electron transport system activity (ETSA), and cyclic voltammetry curve (CV) confirmed that the MRHB improved the electron transfer and membrane activity of strain XL4.